2010
DOI: 10.1111/j.1346-8138.2010.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid-mediated photodynamic therapy to superficial malignant skin tumors using Super Lizer

Abstract: Photodynamic therapy (PDT) using topically applied 5-aminolevulinic acid (ALA) has become a generally accepted treatment modality for superficial malignant skin tumors. However, the costly excimer-dye laser, diode laser and light-emitting diode (LED) frequently used to administrate PDT are impractical to use in most dermatology clinics. This study evaluated the effectiveness of ALA-mediated PDT using a Super Lizer (Tokyo Iken, Tokyo, Japan) equipped with band-pass filters in 38 patients with superficial malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
(45 reference statements)
0
11
1
Order By: Relevance
“…Previous studies showed that the efficacy of ALA-PDT in Asian patients was similar to that in Caucasian patients18,19,20,23. However, higher light doses, longer irradiation times, and several treatment sessions were required because melanin absorbs the light intended for protoporphyrin IX (PpIX) in dark skin types18,19,20,23. Because there are differences in the long-term efficacy and safety of PDT between Asian and Caucasian populations, data obtained from Caucasians cannot necessarily be applied to the Asian population.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Previous studies showed that the efficacy of ALA-PDT in Asian patients was similar to that in Caucasian patients18,19,20,23. However, higher light doses, longer irradiation times, and several treatment sessions were required because melanin absorbs the light intended for protoporphyrin IX (PpIX) in dark skin types18,19,20,23. Because there are differences in the long-term efficacy and safety of PDT between Asian and Caucasian populations, data obtained from Caucasians cannot necessarily be applied to the Asian population.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies on MAL-PDT have shown complete response rates of 69% to 92% for AKs on the face and scalp of Caucasian populations10,14,15,16,17. To date, there have been insufficient studies on dark-skinned ethnic groups that have demonstrated the efficacy of ALA-PDT for AKs18,19,20,23. Nakano et al18 showed that ALA-PDT is useful for the treatment of AKs in Asians, and its efficacy might depend on the lesion size and histopathological severity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations